Functional Connectivity Differences of the Subthalamic Nucleus Related to Parkinson's Disease. Issue 3 (24th December 2015) - Mathys, Christian; Caspers, Julian; Langner, Robert; Südmeyer, Martin; Grefkes, Christian; Reetz, Kathrin; Moldovan, Alexia‐Sabine; Michely, Jochen; Heller, Julia; Eickhoff, Claudia R.; Turowski, Bernd; Schnitzler, Alfons; et al.
Abstract: A typical feature of Parkinson's disease (PD) is pathological activity in the subthalamic nucleus (STN). Here, we tested whether in patients with PD under dopaminergic treatment functional connectivity of the STN differs from healthy controls (HC) and whether some brain regions show (anti‐) correlations between functional connectivity with STN and motor symptoms. We used functional magnetic resonance imaging to investigate whole‐brain resting‐state functional connectivity with STN in 54 patients with PD and 55 HC matched for age, gender, and within‐scanner motion. Compared to HC, we found attenuated negative STN‐coupling with Crus I of the right cerebellum and with right ventromedial prefrontal regions in patients with PD. Furthermore, we observed enhanced negative STN‐coupling with bilateral intraparietal sulcus/superior parietal cortex, right sensorimotor, right premotor, and left visual cortex compared to HC. Finally, we found a decline in positive STN‐coupling with the left insula related to severity of motor symptoms and a decline of inter‐hemispheric functional connectivity between left and right STN with progression of PD‐related motor symptoms. Motor symptom related uncoupling of the insula, a key region in the saliency network and for executive function, from the STN might be associated with well‐known executive dysfunction in PD. Moreover, uncoupling between insula and STN might also induce an insufficient setting of thresholds for the discrimination between relevant and irrelevant salient environmental stimuli, explaining observations of disturbed response control in PD. In sum, motor symptoms in PD are associated with a reduced coupling between STN and a key region for executive function. Hum Brain Mapp 37:1235–1253, 2016 . © 2015 Wiley Periodicals, Inc .